Можга. Горок над Сюгинкой - рекой: массово-политическое издание / А. Г. Вичужанин - Вичужанин А. Г. (Удмуртия, 2001)
Экземпляры: б/ф №4 () / Инвентарный номер: 35929 / Цена: 40.00 / Авт.знак: В 54 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)